STRATEGI KREATIF GURU BAHASA ARAB DALAM MENUMBUHKAN MINAT BELAJAR SISWA DI MTS MUHAMMADIYAH 05 KALIKUNING - Saifudin, Muhammad; Alwi, Itsnaini Muslimati (Universitas KH. Mukhtar Syafaat, 2025)
This study aims to analyze the creative strategies implemented by Arabic language teachers in fostering students' learning interest at MTs Muhammadiyah 05 Kalikuning. Using a descriptive qualitative method, data were collected through semi-structured interviews with Arabic language teachers, observations of the learning process in the classroom, and documentation analysis. The results showed that teachers implemented various creative strategies such as a communicative approach, the use of technological learning media, educational games, and group-based learning. This study found that these creative strategies contributed significantly to increasing students' learning interest, which was marked by higher enthusiasm in learning Arabic. However, some students still experienced difficulties due to the complexity of grammar and differences in language structure. This study suggests the need for institutional support in the form of increasing the allocation of learning time and training in the use of educational technology for teachers to further optimize creative learning strategies.